High quality draft genome sequence of Staphylococcus cohnii subsp. cohnii strain hu-01 - Hu, XinJun (Michigan State University, 2014)
Staphylococcus cohnii subsp. cohnii belongs to the family Staphylococcaceae in the order Bacillales, class Bacilli and phylum Firmicutes. The increasing relevance of S. cohnii to human health prompted us to determine the genomic sequence of Staphylococcus cohnii subsp. cohnii strain hu-01, a multidrug-resistant isolate from a hospital in China. Here we describe the features of S. cohnii subsp. cohnii strain hu-01, together with the genome sequence and its annotation. This is the first genome sequence of the species Staphylococcus cohnii.